Sistem Pendukung Keputusan Pembuatan Pusat Oleh-oleh Menurut Kecamatan di Temanggung menggunakan Metode SAW - Bramastya Arya Gandhi Rusmantara; Adi Nugroho (LPPM STIKOM Tunas Bangsa, 2023)
Indonesia's economic condition, especially in Temanggung Regency, has experienced a significant increase, including in the tourism sector after the COVID-19 pandemic. This study aims to find out the best sub-districts in the Temanggung district as places for the construction of souvenir centers that can support the tourism sector. This study uses the SAW method and quantitative methods to determine the best decision. Data processing in this study was assisted by using Microsoft Excel. The data for this study used 19 sub-districts in the Temanggung district. The data that has been processed produce the best decision for the construction of souvenir centers in Temanggung district, namely, Ngadirejo District (A12; 129.16667), Kedu District (A9; 126.6667), and Parakan District (A13; 126.6667). Further researchers can develop this research by combining several decision support methods such as AHP, ELECTRE, or PROMETHEE with the SAW method. This research is expected to help related parties to develop the development of a souvenir center as a support for the tourism sector in Temanggung district